Peran Kelompok Wanita Tani dan Kontribusi Laki-Laki Terhadap Keadilan Gender di Kabupaten Bener Meriah - Mursyidin, Mursyidin; Hafni, Nur; Mardhiah, Ainol; Yulianda, Riki; Darmansyah, Dedy; Prayogi, Aldi; Rivandi, Agung (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
Farmer groups play a crucial role in supporting gender justice in Cavendish banana and coffee businesses. They focus not only on production but also on empowering women across various aspects of the business, from harvesting to coffee sorting. Programs implemented aim to improve group welfare while considering gender equality and enhancing family economic welfare. In managing these businesses, farmer groups involve local communities as laborers, creating opportunities for women to actively participate in production processes through the development of supportive infrastructure and resources. This research aims to identify the roles of men and women within the social and economic structure and their impact on gender equality in Cavendish banana and coffee activities. The research method used is literature study, gathering data from relevant books and sources. The findings indicate that the contributions of both men and women are mutually necessary. For example, the Women's Farmer Group (KWT) in coffee management requires male labor to facilitate their work, highlighting the importance of gender collaboration in enhancing business effectiveness.